The God Card: Strategic Employment of Religious Language in U.S. Presidential Discourse - Ceri Hughes (International Journal of Communication, 2019)
The United States, despite official separation of church and state, is a country dominated politically by Christianity. This is evident in the almost unbroken ranks of Christians elected to the presidency; Christianity is currently a prerequisite to reach the office and a factor of salience when in office. Presidential discourse is frequently infused with religious language. Content analysis of 106 “high-state” and 342 “minor-state” presidential addresses from Roosevelt to Trump provides evidence to illustrate how such language may be employed strategically. The use of general religious language and explicit references to God sharply escalated from the Reagan presidency, and, somewhat surprisingly, it is Donald Trump who is shown to have the highest rate with both these measures. There is also suggestion that this language may have been employed by some presidents to help trespass into areas of opposition strength.